Radiation cooling thin film material with refractive index gradient structure and preparation method of radiation cooling thin film material
By mixing the porous material with ultraviolet cured optical glue and preparing it by light-induced phase separation method, the existing radiation-cooled thin film materials have been solved, and the efficient and low-cost radiation cooling effect is achieved.
Patent Information
- Application Number
- CN202411892527.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
The preparation process of existing radiation-cooled film materials is complex, has high cost and unstable performance, and it is difficult to widely promote in various application fields.
A mixture of porous material and ultraviolet cured optical glue is used to prepare a radiation-cooled film with a gradient structure of refractive index by a light-induced phase separation method, achieving low cost, low thermal conductivity and high efficiency radiation cooling.
It improves the reflectivity and emissivity of the film in the solar band and infrared band, enhances the cooling effect of the target object, simplifies the preparation process, reduces production costs, and is suitable for a variety of application fields.
Smart Images

Figure CN119751936A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new energy and energy-saving technology, and specifically relates to a radiation cooling film material with a refractive index gradient structure and a preparation method thereof. Background Art
[0002] Radiative cooling film is a material that achieves a cooling effect by radiating heat from the surface of an object into outer space. Compared with traditional mechanical refrigeration methods, radiative cooling film can achieve passive cooling without consuming electrical energy, and has significant energy-saving and environmental protection advantages. With the increasing global requirements for energy efficiency and environmental protection, radiative cooling films have shown great application potential in fields such as construction, electronic equipment, and transportation. The basic principle of radiative cooling is to use the natural heat sink of outer space to radiate the heat of an object into outer space through the atmosphere. Since the atmosphere is composed of a variety of gases, these gas molecules will strongly absorb infrared radiation in certain bands and hinder heat radiation, so radiative cooling needs to be achieved in the band with high atmospheric transmittance, the so-called "atmospheric window". Current radiative cooling materials mainly use the atmospheric window band of 8~13 μm.
[0003] In recent years, the daytime radiation cooling method has attracted extensive attention from researchers at home and abroad. Raman et al. (Raman, Nature , VOL515, 2014) proposed a multilayer structure of seven alternating layers of HfO2 and SiO2 with different thicknesses, with a solar spectrum reflectivity of up to 97% at above 850 W / m 2 Under direct sunlight, it can be cooled to 4.9℃ below the ambient temperature; Zhai et al. Science , 2017, 355(6329): 1062-1066) prepared a polymer composite SiO2 microsphere material, which not only achieved a cooling effect below ambient temperature during the day, but also mass-produced the composite material through a roll-to-roll method, effectively reducing the cost of use; Mandal et al. (Mandal J. et al., Science , 2018, 362(6412): 315-319) prepared a porous polymer coating, the emissivity curve of which is close to the ideal curve of radiative cooling above ambient temperature. The reflectivity in the solar spectrum range reaches 96%, and the emissivity in the long-wave infrared (LWIR) band reaches 97%. The coating can make the target object reach an effect of 6 ℃ below the ambient temperature.
[0004] Although the radiation cooling film technology has achieved certain development, it still faces many challenges and shortcomings in practical applications: the preparation process of radiation cooling film usually involves multiple complex physical and chemical treatment processes, such as high-temperature sintering, sputtering coating, chemical vapor deposition, etc. These processes not only require expensive equipment and strict environmental control, but also have problems such as long process flow and low production efficiency; moreover, the cooling performance of the radiation cooling film is easily affected by external environmental factors (such as humidity, pollutant deposition, sunlight exposure, etc.), resulting in unstable cooling effect. The preparation process is complex, the cost is high, and the performance is unstable. Therefore, an efficient thin film material for radiation cooling and its low-cost preparation method are necessary. Summary of the invention
[0005] In view of the problems in the above-mentioned prior art, the purpose of the present invention is to provide a radiation cooling film material with a refractive index gradient structure, high solar reflectivity, and high infrared emissivity, and a low-cost preparation method thereof. The present invention prepares a passive cooling film by a light-induced phase separation method, which can radiate the heat of outdoor objects into the universe through the atmospheric window on a sunny day; it has a porosity gradient and a refractive index gradient structure, which is conducive to radiating the internal heat of the target object outward in the form of infrared rays, greatly improving the power of radiation cooling and increasing the cooling range of the target object; it can achieve a reflectivity of ≥85% in the solar band (300-2500 nm) and an emissivity of ≥92% in the infrared band (8-13 μm); the method of the present invention has the characteristics of low production cost and easy implementation, and is suitable for a variety of application fields.
[0006] The present invention adopts the following technical solution.
[0007] The present invention provides a method for preparing a radiation cooling film material with a refractive index gradient structure, comprising the following steps: (1) Fully mixing a porous material having high porosity and low thermal conductivity with a UV-curable optical adhesive to obtain a uniform dispersion; (2) coating the dispersion on a substrate; (3) curing the dispersion coated on the substrate by ultraviolet light irradiation to obtain a porosity gradient radiation cooling film having a refractive index gradient structure; wherein: In step (1), the porosity of the porous material is greater than 50%, and the thermal conductivity is less than 0.5 W / m·K; the average particle size of the porous material ranges from 1 to 100 μm, and the cavities inside the porous material are randomly distributed, and the cavity diameter is between 10 and 1000 nm.
[0008] In the present invention, in step (1), the porous material is any one of porous silica, porous silicon, porous aluminum, aluminum oxide, porous polymer (such as polystyrene (PS), polyurethane (PU), polyethylene (PE), etc.) or porous carbon; the material composition of the porous material will affect the reflectivity and emissivity of the film, and significantly affect the radiation cooling effect; different porous materials have different porosity, thermal conductivity, radiation emissivity and other characteristics, which directly affect the thermal management performance of the film. Materials with higher porosity can reduce thermal conductivity, while smaller pores may help to better control radiation heat transfer. Selecting a suitable porous material can improve the thermal isolation and radiation cooling effect of the film; the porous material is spherical, cylindrical, fibrous or irregular in shape. Different shapes will affect the preparation process and performance. Spherical materials are relatively more ideal in preparation and dispersion.
[0009] In the present invention, in step (1), the UV-curable optical adhesive includes any one or more resins selected from epoxy acrylate, polyurethane acrylate, polyester acrylate or acrylate. The UV-curable resin in the present invention has low thermal conductivity, high infrared emissivity and good temperature resistance, and can ensure the stability of the film and the long-lasting radiation cooling ability.
[0010] In the present invention, in step (1), the UV-curing optical adhesive is UV-curing optical adhesive Norland 61.
[0011] In the present invention, in step (1), the mass ratio of the porous material to the UV curing adhesive is 1:1 to 1:3.
[0012] In the present invention, in step (2), the substrate is any one of glass, silicon wafer, aluminum sheet or organic glass; the dispersion is coated on the substrate by a scraping method or a spin coating method.
[0013] In the present invention, in step (3), the power of the ultraviolet lamp is 10W and the irradiation time is 15-45s.
[0014] In the present invention, in step (3), the thickness of the radiation cooling film is between 0.4 and 1.5 mm.
[0015] The present invention also provides a radiation cooling film material obtained by the above-mentioned preparation method. Since the porosity of the obtained film material has a gradual change characteristic, the refractive index also presents a gradual change structure. When the internal heat of the target object propagates outward in the form of infrared light, the refractive index gradually decreases from the refractive index value of the target object to the refractive index of the environment, which can effectively reduce the interface reflection effect of the infrared light, thereby enhancing its ability to radiate outward.
[0016] Furthermore, the present invention provides an application of the above-mentioned radiation cooling film material in building energy conservation and thermal management of electronic equipment.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention prepares a stable, low-thermal-conductivity, and porosity-gradient film structure material based on porous materials and ultraviolet light-curing adhesive. The film structure is a refractive index gradient structure. When the internal heat of the target object propagates outward in the form of infrared light, the refractive index gradually decreases from the refractive index of the target object to the ambient refractive index, which can effectively reduce the interface reflection of the infrared light, thereby enhancing its ability to radiate outward, thereby improving the thermal emissivity of the material.
[0018] The radiation cooling film material prepared by the present invention exhibits a good cooling effect and is very suitable for radiation cooling.
[0019] The material preparation process of the invention is simple, low in cost, easy to produce on a large scale, and can be widely used. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Flow chart of the preparation of the radiation cooling film in an embodiment of the present invention.
[0021] Figure 2 This is a cross-sectional electron microscope scanning image of the radiation cooling film in an embodiment of the present invention.
[0022] Figure 3 1 and 1 are test diagrams of the optical properties of the radiative cooling film at different mass ratios in an embodiment of the present invention, wherein (a) is the reflectivity spectrum in the solar band, and (b) is the emissivity spectrum in the infrared band.
[0023] Figure 4 The optical property test diagrams of the radiation cooling film at different thicknesses in the embodiment of the present invention, wherein (a) is the reflectivity spectrum in the solar band, and (b) is the emissivity spectrum in the infrared band.
[0024] Figure 5 This is a diagram showing the cooling effect of the radiation cooling film in an embodiment of the present invention. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0026] 1. Experimental raw material selection Select porous materials, UV-curable optical adhesives and substrates with high porosity and low thermal conductivity; In a specific embodiment, the porous material is made of hollow silicon dioxide micro-nanosphere particles. The silicon dioxide material can effectively It can emit solar radiation (especially 300-2500 nm band) and has a high emissivity in the infrared band (8-13 μm); the size parameter of silica is an average particle size of about 8.6 μm, hollow, and the diameter of the internal cavity is about 10 nm and is randomly distributed; the commercial name and model of UV-curable optical adhesive is Norland 61, which is an easily curable polyurethane-related resin-based mixture; the substrate is a glass substrate.
[0027] 2. Preparation process like Figure 1 As shown, the specific process is as follows: a. Raw material processing: Evenly mix the porous material and UV-curable optical adhesive to form a stable dispersion.
[0028] b. Ultrasonic treatment: The dispersion was thoroughly ultrasonically mixed in an ultrasonic machine for 1 hour.
[0029] c. Thin film coating: Use blade coating, spin coating and other methods to coat the mixed dispersion on a suitable substrate.
[0030] The specific scraping parameters are as follows: scraper gap: 0.2~1.0 mm; scraping speed: 5~20 mm / s; coating thickness: 0.4~1.5 mm; controlled by adjusting the scraper gap and the amount of dispersion applied; Coating environment: Temperature: 20~25℃; Relative humidity: 40%~60%; Avoid strong light and dust environment to ensure the stability of dispersion and the surface quality of film.
[0031] d. Irradiation curing: Use a 10 W UV lamp (central wavelength 365 nm), keep the lamp 5 to 15 cm away from the film surface, and irradiate for about 15 to 45 seconds to ensure that the film is completely cured and obtain a uniform radiation cooling film.
[0032] 3. Performance Test The radiation cooling effect of the prepared radiation cooling film was verified through spectral testing, electron microscope scanning and temperature reduction testing.
[0033] Figure 2 The cross-sectional electron microscope image of the prepared radiation cooling film is shown. Figure 2It can be seen that the silica micro-nano hollow spheres are evenly distributed, and the porous material and UV-curing optical adhesive used are fully mixed. Due to the different refractive indices of the two materials, the duty cycle gradually increases from the substrate to the film material and then to the air, forming a film layer with a gradual porosity characteristic, and the refractive index also presents a gradual structure. Since the film layer has a gradual refractive index structure, when infrared light passes through such a film layer, the refraction of the infrared light will change, which is specifically manifested in the slowing down of the propagation speed of light, and the possible change in reflectivity or transmittance. The gradual decrease in the refractive index can reduce the reflection of infrared light, enhance its ability to radiate outward, effectively improve the thermal emissivity of the film material, and indicate that the film is very suitable for radiation cooling and refrigeration applications in terms of microstructure.
[0034] Again, the reflectivity and emissivity of the prepared cooling film were tested. By controlling the sample thickness to be the same and the mass ratio of the porous material to the UV-curing optical adhesive to be different, multiple samples were obtained for optical testing. Figure 3 shown. Figure 3 (a) is a test chart of the reflectivity of the sample in the solar band, indicating that the reflectivity of the radiation cooling film in the solar band is as high as over 80%. When the mass ratio of the porous material to the UV-curing optical adhesive is 1:1.5, the reflectivity is as high as about 85%; Figure 3 (b) is a test chart of infrared band emissivity. In the atmospheric window range of 8-13 μm, the infrared emissivity of the film is as high as about 92%. This is due to the increase in the thermal emissivity of the film material due to the internal structure with a gradient refractive index. However, the effect of different mass ratios on the infrared band emissivity of the material is not obvious. The design of this material is very suitable for radiation cooling and is an ideal radiation cooling material.
[0035] At the same time, in order to explore the effect of thickness on the optical properties of the cooling film, the mass ratio of porous material to UV-curable optical adhesive was fixed at 1:1.5, and samples with different thicknesses of 0.05, 0.15, 0.25, 0.4, 0.8 and 1.1 mm were prepared to observe the changes in solar reflectivity and infrared emissivity. The spectrum of solar reflectivity changing with thickness is shown in Figure 2. Figure 4 The results show that the change in thickness has a great influence on the reflectivity of the prepared film in the solar band. When the thickness is 1.1 mm, the reflectivity is as high as about 94%, while when the thickness is 0.05 mm, the reflectivity is only about 40%, indicating that the thicker the thickness, the higher the reflectivity of the corresponding film in the solar band. Figure 4 (b) It can be seen that the emissivity of the measured samples in the mid-infrared band is around 90%, indicating that changing the film thickness has no obvious effect on the emissivity in the infrared band, indicating that the material is an excellent radiation cooling material with good application potential.
[0036] Finally, the cooling effect of the prepared cooling film was tested. The test was carried out from 11:00 am to 3:00 pm on September 1, 2024 in Shanghai (31°N). 。 14', 121 E. 。 29') by comparing the temperature changes of room temperature, substrate glass and cooling film under direct sunlight over time. Figure 5 Indicated. The results show that the temperature of the prepared cooling film sample has a temperature difference of about 8-10 ℃ compared with room temperature and glass. The test sample was continuously exposed to the sun. Because the glass substrate material absorbed heat, its test temperature was the highest, even higher than the surrounding air temperature. At around 12 noon, the temperature of the glass reached a maximum of about 70 ℃, while the temperature of the prepared cooling film was only about 55 ℃, indicating that the proposed material has a good cooling effect. At the same time, the solar irradiance on the test day was 796.9 W / m², and the calculated radiation cooling power of the film material was 76.7 W / m 2 , showing a good cooling effect, very suitable for radiation cooling. In addition, the material preparation process is simple, low cost, easy to large-scale production, can promote its application.
[0037] The above is only a specific implementation of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.
Claims
1. A method for preparing a radiation cooling film material with a refractive index gradient structure, characterized in that: The following steps are involved: (1) Fully mixing a porous material having high porosity and low thermal conductivity with a UV-curable optical adhesive to obtain a uniform dispersion; (2) coating the dispersion on a substrate; (3) curing the dispersion coated on the substrate by ultraviolet light irradiation to obtain a porosity gradient radiation cooling thin film material having a refractive index gradient structure; wherein: In step (1), the porosity of the porous material is greater than 50%, and the thermal conductivity is less than 0.5 W / m·K; the average particle size of the porous material ranges from 1 to 100 μm, and the cavities inside the porous material are randomly distributed, and the cavity diameter is between 10 and 1000 nm.
2. The method for preparing the radiation cooling thin film material according to claim 1, characterized in that: In step (1), the porous material is any one of porous silica, porous silicon, porous aluminum, aluminum oxide, porous polymer or porous carbon; the porous material is spherical, columnar, fibrous or irregular in shape.
3. The method for preparing the radiation cooling thin film material according to claim 1, characterized in that: In step (1), the UV-curable optical adhesive includes any one or more resins selected from epoxy acrylate, polyurethane acrylate, polyester acrylate or acrylate.
4. The method for preparing the radiation cooling thin film material according to claim 1, characterized in that: In step (1), the UV-curing optical adhesive is Norland 61 UV-curing optical adhesive.
5. The method for preparing the radiation cooling thin film material according to claim 1, characterized in that: In step (1), the mass ratio of the porous material to the UV curing adhesive is 1:1 to 1:
3.
6. The method for preparing the radiation cooling thin film material according to claim 1, characterized in that: In step (2), the substrate is any one of glass, silicon wafer, aluminum sheet or organic glass; the dispersion is coated on the substrate by a scraping method or a spin coating method.
7. The method for preparing the radiation cooling thin film material according to claim 1, characterized in that: In step (3), the power of the UV lamp is 10W and the irradiation time is 15-45s.
8. The method for preparing a radiation cooling thin film material according to claim 1, characterized in that: In step (3), the thickness of the radiation cooling film is between 0.4 and 1.5 mm.
9. A radiation cooling film material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the radiation cooling film material according to claim 9 in building energy conservation and thermal management of electronic equipment.